Staphylococcus aureus carriage is associated with microbiome composition in the nares and oropharynx, not the hand, of monozygotic twins - Dalman, Mark R.; Simison, W. Brian; Nielsen, Danny; Bhatta, Sabana; Ramahi, Noor; Yee, Clair; Thapaliya, Dipendra; Kadariya, Jhalka; Cheatham, Shanice; Olson, Hailee; Smith, Tara C. (Frontiers in Microbiomes, 2025)
BackgroundStaphylococcus aureus is a gram-positive bacterium commonly found in the nares and oropharynx of one in three individuals and has the potential to cause significant health problems. With antibiotic-resistant strains causing 11,000 deaths yearly and 2% of the population nasally colonized with methicillin-resistant S. aureus, a search for predictive markers and associative relationships between carriage have been long-sought goals. Within our study, we leveraged monozygotic twin participants in concert with multi-site microbiome analyses to characterize the impacts of S. aureus on composition.ResultsWe recruited 147 monozygotic twin pairs and characterized three sites, i.e., the nares, oropharynx, and hand microbiomes, using 16S rRNA v3-v4 sequencing in addition to S. aureus carriage status. The prevalence of S. aureus was highest in the oropharynx followed by nares and hand with concordance between twin pairs highest in the nares, followed by oropharynx. The detection of S. aureus was statistically correlated with differences in microbiome composition across sites, as indicated by beta diversity and DESeq2 analyses. Microbiome composition was most similar in twins’ nares that were S. aureus culture-positive concordant, whereas twins that were culture-negative concordant had the most similarity in the oropharynx. Of significance, Moraxella nonliquefacians and Capnocytophaga were inversely associated with S. aureus in the nares and oropharynx, respectively.ConclusionsThis improved understanding of S. aureus colonization in nares, oropharynx, and hand microbiomes in monozygotic twin pairs is a further step towards unraveling the degree to which the microbiome is influenced by host genetics and S. aureus carriage.